2020
DOI: 10.1371/journal.pmed.1003351
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy obesity, transition to unhealthy metabolic status, and vascular disease in Chinese adults: A cohort study

Abstract: Background Metabolically healthy obesity (MHO) and its transition to unhealthy metabolic status have been associated with risk of cardiovascular disease (CVD) in Western populations. However, it is unclear to what extent metabolic health changes over time and whether such transition affects risks of subtypes of CVD in Chinese adults. We aimed to examine the association of metabolic health status and its transition with risks of subtypes of vascular disease across body mass index (BMI) categories. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 42 publications
(48 reference statements)
7
105
2
1
Order By: Relevance
“…Individuals with obesity constitute a heterogeneous population and the concept of “metabolically healthy obesity” has been discussed frequently in existing medical literature [ 39 41 ]. However, a cohort study, which was performed among Chinese adults, showed that individuals with metabolically healthy obesity had an increased risk of major cardiovascular events and that 40% of them transitioned to metabolically unhealthy obesity health status during a 10-year follow up [ 40 ]. A recent large case-control cohort analysis found that, irrespective of metabolic health, people with overweight and obesity had higher CHD risk than their counterparts with normal weight, thus challenging the concept of “metabolically healthy obesity” [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with obesity constitute a heterogeneous population and the concept of “metabolically healthy obesity” has been discussed frequently in existing medical literature [ 39 41 ]. However, a cohort study, which was performed among Chinese adults, showed that individuals with metabolically healthy obesity had an increased risk of major cardiovascular events and that 40% of them transitioned to metabolically unhealthy obesity health status during a 10-year follow up [ 40 ]. A recent large case-control cohort analysis found that, irrespective of metabolic health, people with overweight and obesity had higher CHD risk than their counterparts with normal weight, thus challenging the concept of “metabolically healthy obesity” [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of MHO was 4.33% and 2.95% in Beijing and Hunan in 2020, respectively. In the China Kadoorie Biobank study, the MHO phenotype accounted for 3.3% of the total population during the period 2004 to 2008 in China [24]. According to a previous study, the prevalence of MHO has been shown to range between 4.2% and 13.6% in a random sample from a Chinese adult population, depending on the de nition used for MHO [25].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Despite the inconsistent findings regarding the association between metabolic health and the risk for diabetes, the unstable nature of MHO may deteriorate to metabolically unhealthy overweight/obesity (MUO) overtime, and ultimately increase the risk for the development of diabetes. [8][9][10] The Nurses' Health Study delineated a decline of healthy metabolic profile with increased age after a 30-year follow-up and suggested an early intervention to impede the transition from healthy to unhealthy metabolic status in both overweight and obese populations. 9 Thus, it is urgent to investigate the shortterm MHO-to-MUO transition impact on the T2D risk and identify the predictors for this imminent transition.…”
Section: Introductionmentioning
confidence: 99%